An Task-Based Learning Implementation through Google Classroom in Senior High School - Kadek Adiarta Parmawan; Ni Nyoman Padmadewi; I G A Lokita Purnamika Utami (Jurnal Ilmiah Pendidikan Profesi Guru, 2022)
The pandemic forces teachers to adjust their teaching methods to the online learning, which includes the implementation of Task-Based Learning. The online implementation would be different from the one in the conventional learning due to the use of learning platform. Therefore, this study was conducted to (1) analyse the implementation of Task-Based Learning through Google Classroom and (2) analyse the problems faced by the teacher in the implementation. This study took one English teacher along with 39 students as the subjects of the study. This study is descriptive qualitative study. The data collected through observation and interviews. The analysis was conducted through three stages, which were data reduction, data display, and conclusion drawing or interpretation. Then to ensure the validity of the findings of this study, the researcher conducted triangulation in the form of triangulation of method. The results indicated that the teacher implemented Task-Based Learning through Google Classroom by following three cycles, including (1) Pre-Task cycle, (2) Task cycle, and (3) Language Focus cycle. It was implemented by using several features on Google Classroom as well as other Google platforms, which was implemented synchronously and asynchronously. Besides that, the teacher faced three main problems related to the large number of students in a class, time limitation, and difficulty in preparing the learning materials.